Identifying the 993–994 CE Miyake Event in the Oldest Dated Living Tree in Europe. Issue 5 (October 2019) - Quarta, Gianluca; Di Filippo, Alfredo; Calcagnile, Lucio; D'Elia, Marisa; Biondi, Franco; Saba, Emanuele Presutti; Baliva, Michele; De Vivo, Giuseppe; Schettino, Aldo; Piovesan, Gianluca
ABSTRACT: Combined dendrochronology and accelerator mass spectrometry radiocarbon (AMS 14 C) dating analyses were used in order to date an old living tree named Italus, growing in the Pollino massif in Southern Italy. Wiggle match AMS 14 C dating analysis was performed on a 320-yr-long floating chronology obtained by cross-dating four wood cores extracted from the exposed roots of the tree. Following this approach, an age for the tree of ≈1230 yr was estimated. This age makes Italus the oldest living tree in Europe. High-resolution 14 C dating analyses performed on single rings extracted from the tree stem allowed us to identify the 993–994 CE large excursion in atmospheric 14 C concentration (Miyake event) revealing for the first time its presence in the Mediterranean basin.